The Mediating Effect of Organizational Culture on the Relationship Between Organizational Commitment and Work-life Balance Among Business Management Faculty - Sabuero, Jimmy B. (Future Science / FSH-PH Publications, 2023)
Work-life balance involves work and family. Work's great obligations require time for friends, family, civic activity, personal growth, self-care, and other personal pursuits. This study aimed to determine the mediating effect of organizational culture on the relationship between organizational commitment and work-life balance among business management faculty. This study used a descriptive correlational research design with mediation analysis. Stratified Random sampling was used with a total sample size of 130 respondents. Data were analyzed through descriptive and inferential statistics using mean and standard deviation. The inferential statistics, Pearson R was used to test the significant relationship, while mediation analysis was used to determine the effect of organizational culture on the relationship between organizational commitment and work-life balance. The findings reveal that the overall mean of faculty’s organizational commitment is (X̄=3.34, SD=0.59), interpreted as